Expansions of Cytotoxic CD4+CD28− T Cells Drive Excess Cardiovascular Mortality in Rheumatoid Arthritis and Other Chronic Inflammatory Conditions and Are Triggered by CMV Infection - Broadley, Iain; Pera, Alejandra; Morrow, George; Davies, Kevin A.; Kern, Florian (Frontiers in Immunology, 2017)
A large proportion of cardiovascular pathology results from immune-mediated damage, including systemic inflammation and cellular proliferation, which cause a narrowing of the blood vessels. Expansions of cytotoxic CD4+ T-cells characterized by loss of CD28 (‘CD4+CD28− T-cells’ or ‘CD4+CD28null cells’) are closely associated with cardiovascular disease (CVD), in particular coronary artery damage. Direct involvement of these cells in damaging the vasculature has been demonstrated repeatedly. Moreover, CD4+CD28− T-cells are significantly increased in rheumatoid arthritis (RA) and other autoimmune conditions. It is striking that expansions of this subset beyond 1-2% occur exclusively in CMV-infected people. CMV infection itself is known to increase the severity of autoimmune diseases, in particular RA and has also been linked to increased vascular pathology. A review of the recent literature on immunological changes in cardiovascular disease, RA, and CMV infection provides strong evidence that expansions of cytotoxic CD4+CD28− T-cells in RA and other chronic inflammatory conditions are limited to CMV-infected patients and driven by CMV-infection. They are likely to be responsible for the excess cardiovascular mortality observed in these situations. The CD4+CD28− phenotype convincingly links CMV infection to cardiovascular mortality based on a direct cellular-pathological mechanism rather than epidemiological association.